Probing the relevance of repeated cathodal transcranial direct current stimulation over the primary motor cortex for prolongation of after‐effects. (9th December 2019) - Mosayebi Samani, Mohsen; Agboada, Desmond; Kuo, Min‐Fang; Nitsche, Michael A.
Abstract : Key points: To explore the capability of cathodal transcranial direct current stimulation (tDCS) to induce late‐phase long‐term depression (LTD) via repeated stimulation. Conventional (1 mA for 15 min) and intensified (3 mA for 20 min) protocols with short (20 min) and long (24 h) intervals were tested. Late‐phase plasticity was not induced by a single repetition of stimulation. Repetition reduced the efficacy of stimulation protocols with higher intensities. Abstract: Transcranial direct current stimulation (tDCS) has shown promising results in pilot studies as a therapeutic intervention in disorders of the central nervous system, but more sustained effects are required for clinical application. To address this issue, one possible solution is the use of repeated stimulation protocols. Previous studies indicated the possibility of extending the after‐effects of single intervention cathodal tDCS by repeating the tDCS, with relatively short intervals between repetitions being most effective. In this study, we thus investigated the effects of repeated stimulation protocols at short and long intervals, for a conventional tDCS protocol (1 mA for 15 min) and a newly developed optimized protocol (3 mA for 20 min). In 16 healthy participants, we compared single interventions of conventional and optimized protocols, repeated application of these protocols at intervals of 20 min and 24 h, and a sham tDCS session. tDCS‐induced neuroplastic after‐effects were then monitored with transcranial magnetic stimulation (TMS)‐induced motor evoked potentials (MEPs) until the following evening after stimulation. The results revealed that the duration of the after‐effects of repeated conventional and optimized protocols with short intervals remained nearly unchanged compared to the respective single intervention protocols. For the long‐interval (24 h) protocol, stimulation with the conventional protocol did not significantly alter respective after‐effects, while it reduced the efficacy of the optimized protocol, compared with respective single interventions. Thus late‐phase plasticity could not be induced by a single repetition of stimulation in this study, but repetition reduced the efficacy of stimulation protocols with higher intensities. This study provides further insights into the dependency of tDCS‐induced neuroplasticity on stimulation parameters, and therefore delivers crucial information for future tDCS applications. Key points: To explore the capability of cathodal transcranial direct current stimulation (tDCS) to induce late‐phase long‐term depression (LTD) via repeated stimulation. Conventional (1 mA for 15 min) and intensified (3 mA for 20 min) protocols with short (20 min) and long (24 h) intervals were tested. Late‐phase plasticity was not induced by a single repetition of stimulation. Repetition reduced the efficacy of stimulation protocols with higher intensities.